Research Note: Testing the validity of latency-to-lie tests without water for objective on-farm assessment of walking ability of broiler chickens - Kaitlin Wurtz; Sigga Rasmussen; Anja Riber (Poultry Science)
The latency-to-lie (LTL) test is an objective method for assessing walking ability of broiler chickens which has traditionally consisted of placing a bird into a tub of shallow water and measuring how long it takes the standing bird to sit, with duration being negatively associated with gait score. Unfortunately, this method is impractical for use on commercial farms. Thus, the aim of this study was to assess the performance of LTL tests without the addition of water, making them more practical for use on farm. In total, 159 Ross 308 and 186 Rustic Gold broilers were assessed. Following receiving a gait score (Bristol scale), birds were placed individually into a litter lined clear plastic storage box and the LTL was conducted with a maximum test duration of 300 s. Following a 120 s period of rest, the bird was then placed on the litter near a group of flockmates, and the LTL test was repeated. This allowed for the assessment of whether containment of the bird was necessary. Latencies to lie were negatively correlated with gait score (With box: ρ=−0.44 , P < 0.001; Without box: ρ=−0.46 , P < 0.001). The latencies to lie (mean ± SD) when using a box were 129.0 ± 82.0, 114.0 ± 78.8, 71.9 ± 54.9, 45.8 ± 35.8, and 7.9 ± 14.0 s and without a box were 104.0 ± 97.2, 52.2 ± 53.8, 27.9 ± 29.9, 22.8 ± 27.0, and 14.0 ± 19.4 s for gait scores 0, 1, 2, 3, and 4, respectively. There was no effect of hybrid on the performance of either of the tests. Results suggest that the LTL tests without water could serve as an objective and valid measure of walking ability on farm, with the LTL test with a box showing better ability at distinguishing between specific gait scores compared to the LTL test without a box, though possible impacts of fatigue due to study design should be considered.